A metagenomic approach to demystify the anaerobic digestion black box and achieve higher biogas yield: a review - Ostos, Iván; Flórez-Pardo, Luz Marina; Camargo, Carolina (Frontiers in Microbiology, 2024)
The use of fossil fuel and the increasing accumulation of organic waste drive the need to explore sustainable energy alternatives. One option is anaerobic digestion, which utilizes secondary biomass to obtain biogas while mitigating greenhouse gas emissions. Given the crucial role of microbial activity in anaerobic digestion, there is a pressing need to deepen the understanding of this microbial community, as it holds key information for biogas production. While metagenomics has emerged as a valuable tool for unravelling microbial composition and opening the possibility of predicting functional potential in biodigestion, it falls short in interpreting functional and metabolic interactions, limiting comprehensive insights of the roles of the individuals in the community. It emphasizes the significance of enhancing metagenomics scope through innovative tools showcasing the often-unnoticed crucial role of microbiota during biomass digestion, that can more accurate elucidate microbial ecological fitness, shared metabolic pathways, and interspecies interactions. By addressing current limitations and integrating metagenomics with other omics approaches, more accurate predictive techniques can be developed, facilitating informed decision-making to optimize AD processes and enhance biogas yields, thus contributing to a more sustainable future.